A Human Skeletal Muscle Atlas Identifies the Trajectories of Stem and Progenitor Cells across Development and from Human Pluripotent Stem Cells - Xi, Haibin (Cell Stem Cell, 2020)
The developmental trajectory of human skeletal myogenesis and the transition between progenitor and stem cell states are unclear. We employed single cell RNA-sequencing to profile human skeletal muscle tissues from embryonic, fetal and postnatal stages. In silico, we identified myogenic as well as other cell types and constructed a “roadmap” of human skeletal muscle ontogeny across development. In a similar fashion, we also profiled the heterogeneous cell cultures generated from multiple human pluripotent stem cell (hPSC) myogenic differentiation protocols, and mapped hPSC-derived myogenic progenitors to an embryonic-to-fetal transition period. We found differentially enriched biological processes and discovered co-regulated gene networks and transcription factors present at distinct myogenic stages. This work serves as a resource for advancing our knowledge of human myogenesis. It also provides a tool for a better understanding of hPSC-derived myogenic progenitors for translational applications in skeletal muscle based regenerative medicine.